Fossombronia isaloensis Cargill & D.A.Callaghan, a new liverwort from sandstone massifs in southern Madagascar. (2nd July 2020) - Cargill, D. Christine; Callaghan, Des A.; Forrest, Laura L.; Reeb, Catherine
ABSTRACT: Introduction . Although Madagascar is known for its unique fauna and vascular flora, the country's bryophyte flora in contrast is understudied and under collected. Arising from a bryophyte collecting expedition undertaken in May–June 2016, this paper describes a new species of simple thalloid liverwort, Fossombronia isaloensis, from Madagascar. Methods . Morphological traits across specimens were reviewed and compared with related species. DNA sequence data from rbc L, rps 4 and trnL-trnF was obtained from 7 accessions of Fossombronia from Madagascar and 18 other named species of the genus and used to produce a plastid-based phylogeny. Results. DNA sequence data show that Fossombronia isaloensis is not closely related to any other Fossombronia taxon sampled for this study. A description and diagnosis is provided and a type specimen designated for the new species. Conclusions. The bryophyte flora of Madagascar urgently deserves further inventory and taxonomic investigation.